The Optimal Use of Exhaustible Resources under Nonconstant Returns to Scale - Serguei Kaniovski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper offers a complete analysis of the welfare-maximizing capital investment and resource depletion policies in the DHSS model with capital depreciation and any returns to scale. We establish a general existence result and show that an optimal admissible policy may not exist if the output elasticity of the resource equals one. We characterize the optimal policies by applying an appropriate version of the Pontryagin maximum principle for infinite-horizon optimal control problems.
Keywords: C61; O38; Q01; Q56; 330